ANALISA PERPINDAHAN PANAS KOTAK PEMANAS DAN PENDINGIN YANG MENGGUNAKAN MODUL TERMOELEKTRIK SEBAGAI SUMBER KALOR - Dani Ikhsan Saputra; Azridjal Aziz (Jurnal Sains dan Teknologi, 2019)
Thermoelectric is the process of converting temperature differences into electrical energy or vice versa. This phenomenonhas been developed into a module so that it can be used as a power plant or cooling and heating device. in the study heattransfer analysis was carried out on heating and cooling boxes using thermoelectric modules as heat sources. The purposeof the heat transfer analysis in cooling and heating boxes is to find out what heat transfer value occurs in hot and coldboxes using thermoelectric modules, while for the variables needed to analyze heat transfer that occurs in heating andcooling boxes 1) dimensions of the heating box and coolant, 2) determine the ambient temperature outside the box andthe performance temperature in the box, 3) calculate the heat transfer value that passes through the wall of the box, 4)calculate the heat transfer outside the box wall box, 5) calculate the heat transfer inside the box wall. The result is a heattransfer analysis that occurs in a heating box, which is 2.28 W and in a cooler of 2.4 W.